2016
DOI: 10.1080/10934529.2015.1128711
|View full text |Cite
|
Sign up to set email alerts
|

Urinary inorganic arsenic concentrations and semen quality of male partners of subfertile couples in Tokyo

Abstract: Inorganic arsenic (iAs) has been known as a testicular toxicant in experimental rodents. Possible association between iAs exposure and semen quality (semen volume, sperm concentration, and sperm motility) was explored in male partners of couples (n = 42) who visited a gynecology clinic in Tokyo for infertility consultation. Semen parameters were measured according to WHO guideline at the clinic, and urinary iAs and methylarsonic acid (MMA), and dimethylarsinic acid concentrations were determined by liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, very wide confidence intervals clearly indicate the uncertainty in the risk estimates. Six additional studies were also evaluated but did not fulfil the inclusion criteria and were accordingly not considered further (Calogero et al, 2021;Oguri et al, 2016;Sengupta et al, 2013;Sukhn et al, 2018;Tian et al, 2021;Xu et al, 2012).…”
Section: Effects On Male Fertilitymentioning
confidence: 99%
“…However, very wide confidence intervals clearly indicate the uncertainty in the risk estimates. Six additional studies were also evaluated but did not fulfil the inclusion criteria and were accordingly not considered further (Calogero et al, 2021;Oguri et al, 2016;Sengupta et al, 2013;Sukhn et al, 2018;Tian et al, 2021;Xu et al, 2012).…”
Section: Effects On Male Fertilitymentioning
confidence: 99%
“…Most research reporting on male infertility was of cross-sectional or ecologic design, having the same methodological challenges as previously described. Arsenic exposure assessment was performed by analysing various metabolites in either urine [16,20,21,54,55], blood [56][57][58] or seminal plasma [57][58][59][60][61], and outcome specification varies greatly making comparisons complex. Findings are generally conflicting, and not consistent.…”
Section: Male Infertility and Semen Quality Parametersmentioning
confidence: 99%
“…The existing literature based on human studies that have investigated the possible reproductive toxicity of arsenic in men is limited. Studies are primarily from ecological or cross-sectional design and results are equivocal [15][16][17][18][19][20][21]. In animal studies, however, significantly lower testicular, epididymal and prostate weight, as well as significantly lower sperm motility and epididymal sperm count when exposed to arsenic through drinking water have been reported [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have 55 reported that arsenic mainly impairs spermatogenesis via aberrant modulation of male 56 reproductive hormones, especially testosterone (Alamdar et al 2017). In humans, 57 arsenic exposure is associated with low semen quality (Oguri et al 2016), infertility 58 (Wang et al 2016), and erectile dysfunction in men (Hsieh et al 2008). There is 59 increasing evidence suggesting that in utero arsenic exposure poses a serious health 60 risk to the developing fetus and newborn (Quansah et al 2015;Shih et al 2017).…”
mentioning
confidence: 99%